Board Characteristics and Environmental Performance - Lin, Feng-Li; Wu, Chia-Wei (Journal of Ecohumanism, 2024)
As corporate priorities transition from traditional financial metrics such as earnings per share (EPS) to an integrated emphasis on environmental, social, and governance (ESG) criteria, both investor and stakeholder expectations have significantly transformed. Modern businesses are increasingly mandated not only to act with urgency but also to cultivate cross-sector partnerships aimed at establishing carbon-reducing ecosystems, thus addressing and mitigating pressing environmental and social risks. Within this shifting landscape, the board of directors assumes a central role, championing sustainable development and strengthening the principles of corporate governance. This study rigorously explores the influence of the board on environmental performance, identifying critical determinants that shape this relationship through a corporate governance lens. Employing a robust random-effects model, this research evaluates a comprehensive panel dataset comprising 5,616 firm-year observations from Taiwan’s electronics sector over the period from 2006 to 2020. Specifically, the study investigates how board size and meeting frequency impact environmental performance metrics. Findings reveal that larger board sizes are positively correlated with enhanced environmental outcomes, whereas meeting frequency does not yield a statistically significant effect on environmental performance. This investigation deepens the theoretical discourse on the intricate nexus between corporate governance and environmental performance while providing actionable insights for corporate leaders and regulatory bodies. By emphasizing the essential role of board composition, particularly board size, this study elucidates the fundamental connection between board structure and a firm’s enduring commitment to sustainability. These findings reinforce a governance framework that promotes long-term ecological stewardship and social responsibility, laying a robust foundation for corporate practices that are both effective and sustainable.